Ancient anger : perspectives from Homer to Galen - Braund, Susanna Morton; Most, Glenn W. (Yale classical studies, 2003)
Anger is found everywhere in the ancient world, starting with the very first word of the Iliad and continuing through all literary genres and every aspect of public and private life. This volume brings together several significant new studies on literary, philosophical, medical, and political aspects of ancient anger.